Influence of the geometric characteristics of wedges on the safety of Vrasna tunnel in Egnatia highway, N. Greece - Chatziangelou, M.; Christaras, B. (Bulletin of the Geological Society of Greece, 2007)
The present paper concerns the influence of the geometric characteristics of the potential wedges on tunnels safety, which are supported by shotcrete and rock bolts, during the excavation of poor and medium quality rock mass, in accordance to RMR classification system. The geological and tectonic data which were used in our estimations were collected in situ during the excavation of Vrasna's tunnel. According to shear test along discontinuities planes, friction angle was considered 21° on schistosity planes and 35° on joint planes. Furthermore, no cohesion was taken into account, as the fractures were, more or less, opened. The orientation and spacing of discontinuities were taken into account for estimating tunnel stability, given that they affect the strength and the quality of the rock mass during the construction. The collected data and the obtained, after elaboration, results were correlated statistically and power regressions were determined